Cortical activation predicts posttraumatic improvement in youth treated with TF-CBT or CCT. (December 2022) - Espil, Flint M.; Balters, Stephanie; Li, Rihui; McCurdy, Bethany H.; Kletter, Hilit; Piccirilli, Aaron; Cohen, Judith A.; Weems, Carl F.; Reiss, Allan L.; Carrion, Victor G.
Abstract: Background: Identifying neural activation patterns that predict youths' treatment response may aid in the development of imaging-based assessment of emotion dysregulation following trauma and foster tailored intervention. Changes in cortical hemodynamic activity measured with functional near-infrared spectroscopy (fNIRS) may provide a time and cost-effective option for such work. We examined youths' PTSD symptom change following treatment and tested if previously identified activation patterns would predict treatment response. Methods: Youth ( N  = 73, mean age  = 12.97, SD  = 3.09 years) were randomly assigned to trauma-focused cognitive behavioral therapy (TF-CBT), cue-centered therapy (CCT), or treatment as usual (TAU). Parents and youth reported on youth's PTSD symptoms at pre-intervention, post-intervention, and follow-up. Neuroimaging data ( N  = 31) assessed at pre-intervention were obtained while youth engaged in an emotion expression task. Treatment response slopes were calculated for youth's PTSD symptoms. Results: Overall, PTSD symptoms decreased from pre-intervention through follow-up across conditions, with some evidence of relative benefit of TF-CBT and CCT over TAU but significant individual variation in treatment response. Cortical activation patterns were correlated with PTSD symptom improvement slopes ( r  = 0.53). In particular, cortical responses to fearful and neutral facial stimuli in six fNIRS channels in the bilateral dlPFC were important predictors of PTSD symptom improvement. Conclusions: The use of fNIRS provides a method of monitoring and assessing cortical activation patterns in a relatively inexpensive and portable manner. Associations between functional activation and youths' PTSD symptoms improvement may be a promising avenue for understanding emotion dysregulation in clinical populations.